Cultural Connotations And Linguistic Creativity In Malaysian English. - Abdul Rahim, Hajar; Awab, Su'ad (2008)
In this paper we will discuss the two faces of Malaysian English (ME) which is used in ,global, and 'global' discourses. Often times, these two interweave to form a common community identity.